Nurses' knowledge of health literacy, communication techniques, and barriers to the implementation of health literacy programs: A cross-sectional study - Nantsupawat, Apiradee; Wichaikhum, Orn‐Anong; Abhichartibutra, Kulwadee; Kunaviktikul, Wipada; Nurumal, Mohd Said; Poghosyan, Lusine (Wiley Online Library, 2020)
Nurses’ health literacy knowledge and communication skills are essential for improving patients’ health literacy. Yet, research on nurses’ health literacy knowledge and perception is limited. The study aimed to evaluate nurses’ health literacy knowledge, communication techniques, and barriers to the implementation of health literacy interventions. A cross‐sectional study was used. A total of 1,697 nurses in 104 community hospitals in Thailand completed self‐report measures. Approximately 55% of the participants had heard about the concept of health literacy; 9% had received formal training specific to interaction with patients with low health literacy. About 50% of the nurses were aware of their patients’ low health literacy; therefore, they applied the recommended communication techniques for them. Delivery of effective health literacy training was hampered by a lack of assessment tools, health literacy training and specialists, educational materials, and health provider time. Hospital administrators, nurse managers, health leaders should develop strategies to create environments and resources supporting health literacy interventions.